Identification of OAT1/OAT3 as Contributors to Cisplatin Toxicity. Issue 5 (8th July 2017) - Hu, S; Leblanc, AF; Gibson, AA; Hong, KW; Kim, JY; Janke, LJ; Li, L; Vasilyeva, A; Finkelstein, DB; Sprowl, JA; Sweet, DH; Schlatter, E; et al.
Abstract: Cisplatin is among the most widely used anticancer drugs and known to cause a dose‐limiting nephrotoxicity, which is partially dependent on the renal uptake carrier OCT2. We here report a previously unrecognized, OCT2‐independent pathway of cisplatin‐induced renal injury that is mediated by the organic anion transporters OAT1 and OAT3. Using transporter‐deficient mouse models, we found that this mechanism regulates renal uptake of a mercapturic acid metabolite of cisplatin that acts as a precursor of a potent nephrotoxin. The function of these two transport systems can be simultaneously inhibited by the tyrosine kinase inhibitor nilotinib through noncompetitive mechanisms, without compromising the anticancer properties of cisplatin. Collectively, our findings reveal a novel pathway that explains the fundamental basis of cisplatin‐induced nephrotoxicity, with potential implications for its therapeutic management.